2019
DOI: 10.21107/agriekonomika.v8i1.5029
|View full text |Cite
|
Sign up to set email alerts
|

Palm Sugar Agribusiness Development Strategy In Tasikmalaya Regency

Abstract: <p>Sugar palm (Arenga Pinnata, MERR) is one of the most valuable commodities in the plantation sector; thus, they have enormous potential to be developed. The agribusiness development of sugar palm should start from the upstream to the downstream. Therefore, a study on the strategies to develop agribusiness of palm sugar is necessary to be conducted. This research is conducted to: 1) identify the internal and external factors, 2) formulate palm sugar agribusiness development strategies, and 3) determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Sedangkan, metode analisis data AHP digunakan untuk menentukan prioritas kriteria, sub kriteria, dan alternatif unit usaha BUMDes Melati melalui perbandingan secara numerik serta penilaian dalam menentukan solusi permasalahan. AHP digunakan untuk menentukan alternatif terbaik dari multi kriteria berdasarkan dugaan dan persepsi para ahli dengan tetap memperhatikan nilai konsistensi (Nuraini & Atmaja, 2019). Analisis data AHP diolah menggunakan software Expert Choice 11 yang mampu menggabungkan hasil perbandingan dengan jumlah responden lebih dari satu.…”
Section: Metode Penelitianunclassified
“…Sedangkan, metode analisis data AHP digunakan untuk menentukan prioritas kriteria, sub kriteria, dan alternatif unit usaha BUMDes Melati melalui perbandingan secara numerik serta penilaian dalam menentukan solusi permasalahan. AHP digunakan untuk menentukan alternatif terbaik dari multi kriteria berdasarkan dugaan dan persepsi para ahli dengan tetap memperhatikan nilai konsistensi (Nuraini & Atmaja, 2019). Analisis data AHP diolah menggunakan software Expert Choice 11 yang mampu menggabungkan hasil perbandingan dengan jumlah responden lebih dari satu.…”
Section: Metode Penelitianunclassified
“…Foss (1997), menyarankan sinergi kemampuan internal dengan peran pemerintah untuk meningkatkan daya saing. Pemerintah dalam hal ini juga sebagai stakeholder pertanian Indonesia bersama industri, pedagang, koperasi, asosiasi, kelompok tani, dan lembaga keuangan (Nuraini & Atmaja, 2019). Peningkatan kesejahteraan petani juga menjadi target sasaran yang hendak dicapai oleh Kementrian Pertanian tahun 2014 (Watemin & Sulistyani, 2015).…”
Section: Pendahuluanunclassified
“…Nuraini et al [9] revealed that institutional strengthening was done as the efforts to develop, empower, and strengthen the farmers, process, marketers, capital, and others, which were hoped to be able to become the protectors for the bargaining position of the farmers. The strategy of product diversification and packaging innovation can be the strategy of palm sugar enterprise that relates to the products by adding various kinds of the product to expand the market target to gain some profits for the farmer and industry.…”
Section: Review Of Literaturementioning
confidence: 99%